Autonomous field management – An enabler of sustainable future in agriculture. (March 2023) - Gackstetter, David; von Bloh, Malte; Hannus, Veronika; Meyer, Sebastian T.; Weisser, Wolfgang; Luksch, Claudia; Asseng, Senthold
Abstract: CONTEXT: Technological innovations in agriculture are mainly driven by the maxim: increase productivity at any costs. Today, in the face of climate change and an unprecedented loss of biodiversity, this approach is reaching its limits. Meeting global nutrition needs while achieving sustainability is one of the greatest challenges for modern agriculture. OBJECTIVE: Autonomous field management represents the next evolutionary step in agricultural technology. It is characterized by an end-to-end automation of agricultural production processes and by that – for the first time in history - independence from labor constraints. Although literature has provided solutions for individual components of these new technological systems, integrating those components into a common, fully autonomous process has not yet been achieved. METHODS: We analyzed the technological, agronomic, environmental, and related, interdisciplinary literature in the context of automated, and digital field crop management. RESULTS AND CONCLUSION: The review shows the disruptive potential of fully autonomous, labor-independent crop management systems to guarantee the required food security by simultaneously allowing sustainable factors to be equally incorporated into the agricultural decision-making process. The integration of multifaceted objectives into a common decision-making process poses a great challenge to human farmers and their capacities. Liberated from labor constraints, autonomous systems have the potential to align decisions with the complex requirements of multiple − even contradicting – goals more easily, and to execute them accordingly without exhaustion. We show barriers that explain, why fully autonomous crop management is not yet present in today's agricultural practice, despite the fact that the majority of technological sub-components has reached a maturity stage beyond the proof of concept. Substantial technological progress will still be required with respect to the robustness in varying application settings and the standardization of interfaces to integrate diverse subsystems. For the adoption of autonomous cropping systems, societal engagement will be required including extensive research and discussion on public acceptance, legal frameworks, and the human farmers' future role as crucial success factors. SIGNIFICANCE: Aligning autonomous cropping systems to domain-overarching objectives can make these technological solutions not only another, next stage of more efficiently producing technologies, but a game changer for new, environmentally sustainable cropping systems. Field management practice can leave the currently persisting, oversimplified management strategies, characterized by large-scale, and standardized field arrangements, toward more complex approaches with small-scale, diversely structured fields, which consider local particularities and the heterogeneity of the natural landscape. Graphical abstract: Unlabelled Image Highlights: Context: This review includes the state of the art in the four most important technology sectors that are needed for autonomous farming. Objective: Robotics, AI, Big Data – the important topics are developing quickly. We show how this technology can positively impact the system. Results: There is a lack of interconnection between different technologies. If this is made possible, it can reconcile sustainability and production. Conclusion: Autonomous field management can produce more resource-efficiently and incorporate objectives such as sustainability. Significance: Many reviews of the individual technologies exist. However, there are hardly any that consider them integrated within a common system.